2019
DOI: 10.1007/s10565-019-09504-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes produced from 3D cultures of umbilical cord mesenchymal stem cells in a hollow-fiber bioreactor show improved osteochondral regeneration activity

Abstract: Animal and clinical studies have shown that mesenchymal stem cells (MSCs) play an important role in cartilage repair. The therapeutic effect of mesenchymal stem cells based therapies has been increasingly demonstrated to exosome-mediated paracrine secretion. Here, we investigated the cellular processes and mechanism of exosomes produced by conventional 2D culture (2D-Exos) and exosomes produced from 3D culture (3D-Exos) of umbilical MSCs (U-MSCs) in a hollowfiber bioreactor for the treatment of cartilage repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
168
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(170 citation statements)
references
References 30 publications
2
168
0
Order By: Relevance
“…222 Yan et al revealed that exosomes from umbilical MSCs (U-MSC-Exos) had potent chondroprotective effects, including stimulating chondrocyte proliferation and migration, increasing matrix synthesis and inhibiting chondrocyte apoptosis. 223 Intra-articular injection of U-MSC-Exos could significantly promote the repair of cartilage defects in vivo. 223 Moreover, their data also showed that the U-MSC-Exos produced from 3D culture exerted a stronger effect on cartilage repair than those from conventional 2D culture.…”
Section: Ultrafiltrationmentioning
confidence: 99%
See 1 more Smart Citation
“…222 Yan et al revealed that exosomes from umbilical MSCs (U-MSC-Exos) had potent chondroprotective effects, including stimulating chondrocyte proliferation and migration, increasing matrix synthesis and inhibiting chondrocyte apoptosis. 223 Intra-articular injection of U-MSC-Exos could significantly promote the repair of cartilage defects in vivo. 223 Moreover, their data also showed that the U-MSC-Exos produced from 3D culture exerted a stronger effect on cartilage repair than those from conventional 2D culture.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…223 Intra-articular injection of U-MSC-Exos could significantly promote the repair of cartilage defects in vivo. 223 Moreover, their data also showed that the U-MSC-Exos produced from 3D culture exerted a stronger effect on cartilage repair than those from conventional 2D culture. 223 In addition, the exosomes of stem cells from human exfoliated deciduous teeth (SHEDs) have been revealed to inhibit inflammatory reactions and maintain anabolism homeostasis in temporomandibular joint chondrocytes via miR-100-5p-mediated mTOR inhibition.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…This suggests that MSCs may not directly differentiate into chondrocytes to participate in tissue repair in vivo, but promote cartilage regeneration through other mechanisms. In recent years, more and more researchers believed that exosomes secreted by MSCs played an important role in cartilage repair and regeneration (Marote et al, 2016;Yan and Wu, 2019;Jin et al, 2020;Liu et al, 2020). Exosomes are generally considered as communication vectors between cells, and carry a large number of complex nucleic acids (mRNA and miRNA lncRNA), proteins and lipids that can regulate and restore extracellular matrix (ECM) homeostasis (Colombo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enriching EVs with specific miRNA as summarised above, other strategies have been used to augment the potency of MSC-EVs in cartilage repair. For instance, three-dimensional culture of UCMSCs in a hollow-fibre bioreactor resulted in a higher yield of EVs and superior therapeutic efficacy in a rabbit cartilage defect model, compared to MSC-EVs from conventional 2D cultures [106]. To ensure that MSC-EVs are retained at the site cartilage injury, human iPSC-EVs have been incorporated with in situ hydrogel glue.…”
Section: Cartilage Regenerationmentioning
confidence: 99%